Depreciations without Exports? : Global Value Chains and the Exchange Rate Elasticity of Exports - Ahmed, Swarnali; Appendino, Maximiliano; Ruta, Michele (World Bank, Washington, DC, 2015)
This paper analyzes how the exchange rate elasticity of exports has changed over time and across countries and sectors, and how the formation of global value chains has affected this relationship. The analysis uses a panel framework covering 46 countries over the period 1996-2012, and first finds evidence that the elasticity of manufacturing export volumes to the real effective exchange rate has decreased over time. The paper then examines whether the formation of supply chains has affected this elasticity using different measures of global value chain integration. Intuitively, as countries are more integrated in global production processes, a currency depreciation only improves the competitiveness of a fraction of the value of final goods exports. In line with this intuition, the analysis finds evidence that the rise of participation in global value chains explains on average 40 percent of the fall in the elasticity, and that corrections of the real effective exchange rate for participation in global value chains do not present the same decreasing pattern in elasticity.